The availability, use of, and need for basic telecommunications in high density, lower income and peripheral urban settlements--Khayelitsha : a case study - Eva, Gary (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA) -- University of Stellenbosch, 1997.